2017
DOI: 10.12659/msm.906038
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Derived Growth Factor Alpha (PDGFRα) Induces the Activation of Cardiac Fibroblasts by Activating c-Kit

Abstract: BackgroundEnhanced platelet-derived growth factor receptor α (PDGFRα) signaling pathway activity leads to cardiac fibrosis. However, because of the pleiotropic effects of PDGFR signaling, its role in mediating the cardiac fibrotic response remains poorly understood. This study aimed to investigate the regulatory effect of c-Kit in cardiac fibroblasts activated by PDGFRα signaling.Material/MethodsA cardiac fibrosis mice model was induced using isoproterenol, and the heart tissues of mice were tested through wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…To determine the functional role of PDGFC in GIST, we treated T1 with recombinant PDGFC (rPDGFC) according to a previously published report [ 31 , 32 ]. PDGFRA phosphorylation was increased by rPDGFC treatment (10 ng/mL), and dose-dependently increased T1 viability (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the functional role of PDGFC in GIST, we treated T1 with recombinant PDGFC (rPDGFC) according to a previously published report [ 31 , 32 ]. PDGFRA phosphorylation was increased by rPDGFC treatment (10 ng/mL), and dose-dependently increased T1 viability (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2e and f ). KIT phosphorylation was also analyzed because PDGFC has been reported to activate KIT signaling via PDGFRA-KIT heterodimerization [ 32 ]. However, rPDGFC did not affect KIT phosphorylation in T1 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, PDGF-AA and TGF-β2 release in CM from dECM-PH was increased compared to dECM-NH. PDGF-AA promotes fibrosis through multiple mechanisms, such as inducing proliferation, myofibroblast polarization, and collagen I synthesis in cardiac fibroblasts [48,49]. TGFβ2, instead, is involved in inducing endothelial-to-mesenchymal transition (EndMT), which is a main mechanism of cardiac fibrosis [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Mayyas, et al have demonstrated the association of endothelin-1 with platelet derived growth factor (PDGF) and connective tissue growth factor (CTGF) [4]. Both of PDGF [16] and CTGF [17] signaling pathways have been reported to be involved in the cardiac fibrosis development. Moreover, the relationship of endothelin-1 and collagen accumulation was also identified by the analysis of Masson’s trichrome stained sections [4].…”
Section: Discussionmentioning
confidence: 99%